2006
DOI: 10.1063/1.2194187
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of sintered clathrate compounds Sr8GaxGe46−x with various carrier concentrations

Abstract: Polycrystalline samples of Sr8GaxGe46−x clathrates with varied nominal Ga contents were prepared by powder metallurgy to produce n-type samples with carrier concentration n of 1.8×1020–1.1×1021cm−3. Their thermoelectric properties were measured in the temperature range from 300to900K. Their Seebeck coefficient and electrical conductivity were found to be typical for a heavily doped semiconductor, and varied systematically with their carrier concentration. The maximum value of the figure-of-merit ZT was 0.62 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
4
31
1
Order By: Relevance
“…The BGG4a sample exhibits a slight increase in charge carrier concentration with temperature, while for BGG4b no trend could be discerned due to large scattering of the data above room temperature. The room temperature charge carrier density for samples BGG1-BGG4a agrees well with what is found in literature, 29,40 while the result for BGG4b is somewhat lower than previously reported for the Ba 8 Ga 16 Ge 30 system.…”
Section: Charge Carrier Density and Mobilitysupporting
confidence: 80%
“…The BGG4a sample exhibits a slight increase in charge carrier concentration with temperature, while for BGG4b no trend could be discerned due to large scattering of the data above room temperature. The room temperature charge carrier density for samples BGG1-BGG4a agrees well with what is found in literature, 29,40 while the result for BGG4b is somewhat lower than previously reported for the Ba 8 Ga 16 Ge 30 system.…”
Section: Charge Carrier Density and Mobilitysupporting
confidence: 80%
“…It has been reported that the thermoelectric properties of type I clathrate vary in a wide range with the stoichiometric composition and homogeneity. For example, the maximum ZT value of Ba 8 Ga 16 Ge 30 synthesized by Martin et al was reported as 0.8 at 850 K [7], while a similar material prepared by Fujita et al only owned maximum ZT of 0.62 at 800 K [3]. Synthesizing homogeneous and reproducible clathrate material with high ZT values is still a challenge.…”
Section: Introductionmentioning
confidence: 95%
“…Since then an increasing number of papers treating the thermoelectric properties of type I clathrates have been published, such as Sr 8 Ga X Ge 46−X , Ba 8 Ga 16 Ge 30 and Eu 8 Ga 16 Ge 30 [3][4][5][6]. It has been reported that the thermoelectric properties of type I clathrate vary in a wide range with the stoichiometric composition and homogeneity.…”
Section: Introductionmentioning
confidence: 98%
“…The optimally doped n-type sample with x = 0.25 has the maximum ZT = 0.86 at 950 K [9,10]. Similarly, Ba 8 Ga 16 Si 30 and Sr 8 Ga 16 Ge 30 exhibit ZT values 0.9 at 870 K and 0.6 at 800 K, respectively [11,12]. These compounds were regarded as examples those fulfill the phonon glass and electron crystal concept proposed by Slack [13].…”
Section: Introductionmentioning
confidence: 98%